Association Between the Electroconductive Value at 24 Acupoints and Blood Pressure in Community-Dwelling Japanese: The Toon Health Study - Michiko Onuma; Kiyohide Tomooka; Isao Saito; Koutatsu Maruyama; Denichiro Yamaoka; Takeshi Tanigawa (Mary Ann Liebert, 2022)
Background: The electroconductive value at acupoints of Ryodoraku theory, which is based on traditional East Asian medicine, pertains to the autonomic nervous system. Case series reported that acupuncture based on Ryodoraku theory lowers blood pressure in hypertensive patients. However, no epidemiological study has been conducted on the association between the electroconductivity and blood pressure. Therefore, this study examined the association between the electroconductive value at the acupoints and blood pressure in community-dwelling Japanese. Materials and Methods: The study participants were 451 men and 950 women aged 30?79 years old, who were not taking antihypertensive medication and who participated in the Toon Health Study from 2011 to 2015. Nationally licensed acupuncturists measured the electroconductive values at 24 acupoints in the hands (H1?6) and feet (F1?6) of participants using a Ryodoraku device. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured with an automatic sphygmomanometer after the participants had rested for 5?min. The association of the electroconductive value at each acupoint with SBP and DBP was examined using sex-specific multiple regression analysis after adjusting for age, body mass index, drinking status, smoking status, physical activity, and menopausal status. Results: In men, borderline significant positive association of the electroconductive values for F4 with SBP was found, and those for F1, F4, and F5 with DBP (p for trend <0.10). In women, significant positive association of the electroconductive values for H2 and F1 with SBP was found, and those for H1, H2, and H3 with DBP (p for trend <0.05). Conclusions: Increased electroconductive values at the acupoints were significantly or borderline significantly associated with the elevation of blood pressure in community-dwelling Japanese. Further longitudinal and interventional studies are needed to elucidate the causal relationship and therapeutic effect on hypertension.